Uruguay : Ex Post Assessment of Longer-Term Program Engagement-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper presents an Ex Post Assessment of Longer-Term Program Engagement for Uruguay. Uruguay has had a series of Stand-By Arrangements that were treated mostly as precautionary between March 1996 and early 2002. These were viewed as a helpful seal of approval, and a vehicle for intensive IMF monitoring. The authorities undertook significant reforms during this period-notably a pension reform, a reduction in public employment, and a lengthening of wage indexation lags. However, other reforms were either not undertaken or completed with a delay.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet